Developing Discovery Learning-Based Assessment Module to Stimulate Critical Thinking and Creativity of Students’ Speaking Performance - Wahyudi, Roni; Rukmini, Dwi; Linggar Bharati, Dwi Anggani (English Education Journal, 2019)
In the teaching and learning process, assessment is considered a critical component of curriculum design to determine whether the goals of education have been achieved. In fact, many teachers still have difficulties to design a suitable assessment instrument. To complicate the matter, it should align with the teaching and learning objectives of the 2013 curriculum which requires the teacher to foster the students' critical and creative thinking. This study aimed to explain the development of discovery-based speaking assessments to stimulate students' critical thinking and creativity at the tenth graders of MIPA 3 at SMA Sultan Agung 1 Semarang in the academic year of 2017/2018. Research and Development (R&D) was applied in this study. This study utilized quantitative and qualitative data through the questionnaire, interview, observation, and test as the instrument in collecting the data. The teacher collaborated with the researcher in developing the discovery-based speaking assessments module. After that, the module was revised based on the experts’ suggestions before conducting the main field testing. The result of the study showed that there were improvements in the students' score after they were taught using discovery-based speaking assessments module. A paired sampled test result yield that there were significant improvements in the students’ mean score in the post-test compared to their pre-test. The significant improvements indicated that discovery-based speaking assessments were effective to improve the students' speaking skill, critical thinking, and creativity.